The Effect of Adipose Tissue-Derived Mesenchymal Stem Cells on Regeneration of Uterine Scars - Bender, R. Ada; Yücel, Aykan; Noyan, Volkan; Gürpınar, Aylin; Atasoy, Pınar; Comu, Faruk (Gynecology Obstetrics & Reproductive Medicine, 2017)
OBJECTIVE: The mesenchymal stem cell application to uterine healing scars may provide better tissue strength. STUDY DESIGN: Hysterectomy was performed on rats, and the wound recovery as a result of primary suturing was evaluated as tissue stretching and the positive histopathological effects. The mesenchymal stem cells originating from the adipose tissue were used during the healing period of the wound and would differentiate to mesenchyme-originated cells present in intact tissue for an optimum level of healing. RESULTS: The weights of non-incised uterine horns in the control group were found to be significantly higher than the weights of the incised uterine horns (z=2.52, p=0.012). In the experiment group, the weights of the incised uterine horns were found to be significantly higher than the non-incised uterine horns (z=2.527, p=0.012). In the control group, the non-incised uterine horns withstood the stretching test to a higher extent than the incised horns, and a significant difference was found between the stretching values (z=2.51, p=0.012). In the experiment group, the incised uterine horns withstood the stretching tests to a higher extent than the non-incised uterine horns; however, there was no significant difference between the stretching tests (z=1.540, p=0.123). CONCLUSION: Adipose tissue-originated mesenchyme stem cells were observed to increase the tissue stretching during wound healing.